In Situ Characterization for Boosting Electrocatalytic Carbon Dioxide Reduction. Issue 10 (9th September 2021) - Cao, Xueying; Tan, Dongxing; Wulan, Bari; Hui, K.S.; Hui, K.N.; Zhang, Jintao
Abstract: The electrocatalytic reduction of carbon dioxide into organic fuels and feedstocks is a fascinating method to implement the sustainable carbon cycle. Thus, a rational design of advanced electrocatalysts and a deep understanding of reaction mechanisms are crucial for the complex reactions of carbon dioxide reduction with multiple electron transfer. In situ and operando techniques with real‐time monitoring are important to obtain deep insight into the electrocatalytic reaction to reveal the dynamic evolution of electrocatalysts' structure and composition under experimental conditions. In this paper, the reaction pathways for the CO2 reduction reaction (CO2 RR) in the generation of various products (e.g., C1 and C2 ) via the proposed mechanisms are introduced. Moreover, recent advances in the development and applications of in situ and operando characterization techniques, from the basic working principles and in situ cell structure to detailed applications are discussed. Suggestions and future directions of in situ/operando analysis are also addressed. Abstract : With an introduction on reaction pathways of CO2 RR for generating various products, recent advances in the development and applications of in situ and operando characterization techniques to reveal the electrocatalytic mechanisms are reviewed, followed by suggestions and future directions of in situ/operando analysis.